The Effect of E-Service Quality on Customer Satisfaction, E-Trust, E-Wom and Repurchase Intention: A Study of Medium-Sized Women Clothing Brands in The Retail Sector - Luis MEGO JARAMILLO; Thaís VALLEJOS ESPINOZA; Pedro BAZO QUINTANA (Communications of International Proceedings, 2022)
The purpose of this research is to determine the relationship between the variable quality of service and the variables electronic trust and consumer satisfaction; in addition to measuring the relationship between these last two variables with electronic word of mouth and the intention to buy back in the context of online sales of women's clothing in the retail sector in the city of Lima. The research considered four dimensions to measure quality of service: website design, online customer service, security-privacy, and reliability. The data was obtained through an online survey of 400 women aged 18 to 35 living in Lima, who had bought clothes online -in the last year- in medium sized independent brand stores. The model was estimated using the partial least squares structural equations (PLS-SEM) technique. The results indicated that quality of service has a direct effect on online consumer trust and satisfaction. Likewise, it was shown that trust has a positive effect on online repurchase intention and electronic word of mouth; however, consumer satisfaction only had a positive effect on repurchase intention, but not on electronic word of mouth.
Keywords: e-Service Quality; Customer Satisfaction; e-Trust; Repurchase Intention; e-wom